Correlation between the dielectric properties and local electronic structure of copper doped calcium titanate - Singh, Jitendra Pal; Gautam, Sanjeev; Kumar, Parmod; Tripathi, Ambuj; Chen, Jin-Ming; Chae, Keun Hwa; Asokan, K. (ELSEVIER SCIENCE SA, 2013)
Copper-doped calcium titanate (CuxCa1-xTiO3, x = 0.0, 0.01, 0.02 and 0.03) ceramic system was synthesized using solid state reaction method. X-ray diffraction and Raman spectroscopic studies reveal the presence of Pbnm space group in the samples. The particle size estimated from scanning electron micrograph changes from 235 nm to 6.5 mu m with copper doping, however crystallite size remain almost constant within experimental error. The dielectric study performed on these samples indicates an increase in the value of dielectric constant with Cu doping. The drastic change in the value of dielectric constant of the samples has been attributed to the change in microstructure. Local electronic structure deduced from X-ray absorption near edge structure reveals no distortion at TiO6 octahedra and reduction in O(2p) and Ca(4sp) hybridized states with increase of Cu2+ doping. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: X-RAY-ABSORPTION; ZINC FERRITE; CATIO3; SPECTROSCOPY; PEROVSKITE; BEHAVIOR; OXIDES; ELNES; RAMAN